Neuronal network oscillations in neurodegenerative diseases - Nimmrich, Volker; Draguhn, Andreas; Axmacher, Nikolai (Neuromolecular medicine, 2015)
Cognitive and behavioral acts go along with highly coordinated spatiotemporal activity patterns in neuronal networks. Most of these patterns are synchronized by coherent membrane potential oscillations within and between local networks. By entraining multiple neurons into a common time regime, such network oscillations form a critical interface between cellular activity and large-scale systemic functions. Synaptic integrity is altered in neurodegenerative diseases, and it is likely that this goes along with characteristic changes of coordinated network activity. This notion is supported by EEG recordings from human patients and from different animal models of such disorders. However, our knowledge about the pathophysiology of network oscillations in neurodegenerative diseases is surprisingly incomplete, and increased research efforts are urgently needed. One complicating factor is the pronounced diversity of network oscillations between different brain regions and functional states. Pathological changes must, therefore, be analyzed separately in each condition and affected area. However, cumulative evidence from different diseases may result, in the future, in more unifying “oscillopathy” concepts of neurodegenerative diseases. In this review, we report present evidence for pathological changes of network oscillations in Alzheimer’s disease (AD), one of the most prominent and challenging neurodegenerative disorders. The heterogeneous findings from AD are contrasted to Parkinson’s disease, where motor-related changes in specific frequency bands do already fulfill criteria of a valid biomarker.
Gesehen am 26.11.2018